Handsanitizer Formulation 70% with the Addition of Natural Performance - Aisyah Mentari; Hafni Nur Insan (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2021)
Background: The use of hand antiseptics in the form of gel preparations among the upper middle class has become a lifestyle. Several hand sanitizer preparations can be found in the market and usually contain a lot of alcohol. The purpose of this study was to formulate a hand sanitizer as an antiseptic. Methods: Handsanitizer formulations were carried out in the pharmacy laboratory of the Aufa Royhan University health faculty in Padangsidimpuan City and then the preparations were tested with preference and allergy tests. Results: Of the 50 panelists, 46 liked the hand sanitizer preparation 70%, while the allergy test carried out showed that 2 panelists did not dare to try because of a history of allergies and 2 people had moderate allergies. Conclusion: Based on the results of acceptability testing and allergy testing, this product can recommended as an antiseptic with a note still have to pay attention to allergic reactions in the wearer.